(untitled) - Sawhney, S.K. (Harlow, England, 2005)
Introductory Practical Biochemistry, designed to cater to the requirements of students of biochemistry, microbiology, molecular biology, cellular biology etc. covers modern techniques employed for qualitative and quantitative analysis of biomolecules. The techniques for genetic transformation etc., have been included to give preliminary information to the beginners in the field of genetic engineering. Radioisotopic and immunological techniques also find a place in the book. Each chapter starts with introductory details of the techniques followed by simple laboratory exercises. The book provides concise information on theoretical and practical aspects of the techniques employed in biochemical studies for the Undergraduate and Postgraduate students, Instructors and Research workers.
Keywords: Biochemistry,Hóa sinh học; Laboratory manuals,Cẩm nang thí nghiệm